The morphology of the pineal gland of the Magellanic penguin (Spheniscus magellanicus Forster, 1781) - Barcelos, R. P.; Filadelpho, A. L. [UNESP]; Baroni, S.; Graça, W. J. (The Brazilian Society of Anatomy (SBA), 2015)
Introduction: The Magellanic Penguin migrates on the ocean currents from its reproduction colonies in Patagonia to seek abundant food on the Brazilian continental shelf. The pineal gland, an endocrine gland, whose secretions are affected by the light-darkness photoperiod, has a basic function in the biological processes of migrating animals. Melatonin, the hormone synthesized and secreted by the pineal gland affects the circadian, circannual and seasonal cycle that directly affects the migration processes of land and sea birds. Materials and Methods: Specimens were collected on the southern coast of Brazil, morphometric assessments and histological analyses of the glands were undertaken. Results: The pineal gland of the Magellanic Penguin lies in a triangular space between the brain hemispheres and the cerebellum and close to the cavernous sinus that follow the region´s dura mater. The average of the pineal gland of the penguins under analysis was 11.16mm and 1,69mm for length and thickness respectively. Test t and the coefficients of co-relationship (r) between the analyzed variables demonstrated that there was no co-relationship between the morphometric variables and the size of the pineal gland (p < 0.05). The Magellanic penguin´s pineal gland has a club-like sacular shape with cells in threads, involved and interlaced by fibrous conjunctive tissues. Conclusion: Results corroborated data in the literature and showed that the pineal gland of these birds is relatively greater than that of other birds and its tissue composition is similar to that of other vertebrates.
Keywords: Birds; Circannual cycle; Migration; Morphometry; Pinealocytes